Aquaculture in Canada The practice and the promise - MacCrimmon, H. R.; Stewart, J. E.; Brett, J. R. (Ottawa, Canada Department of the Environment Fisheries and Marine Science, 1974)
Bulletin of the Ffisheries Research Board of Canada; Bulletin 188
Keywords: Aquaculture